Accelerating global city commitments and actions on climate change - Benjamin Leffel; Benjamin K. Sovacool (Energy and Climate Change, 2026)

Cool cities, local contexts: A typology of cooling interventions across the disciplines to address extreme heat and decarbonization in urban areas - Melissa A. Martin; Benjamin K. Sovacool (Energy and Buildings, 2026)

Towards a typology of residential energy consumers: Social context and awareness as predictors of energy-efficient household behaviors in the United States - Erin Heinz; Benjamin K. Sovacool; Thomas Kwan; Johan Nordensvärd; Frauke Urban; Muhammad Asif; Weimin Zhang; Patrik Thollander; Patrik Rohdin; Niklas Arvidsson (Ecological Economics, 2026)

Sustainable development and Africa’s critical minerals: A multi-framework approach - Macdonald Amoah; Benjamin Sovacool; Zainab Usman; Abay Yimere; Cullen S. Hendrix; Nathaniel Dolton-Thornton; Karla Cervantes Barron; Morgan Bazilian; John Ayaburi; Clarkson Kamurai (The Extractive Industries and Society, 2026)

Achieving net-zero for artificial intelligence: Big-tech's sustainability challenges from 2030 to 2050 - Can Hankendi; Ayse K. Coskun; Benjamin K. Sovacool (Journal of Cleaner Production, 2026)

Reflecting on the politics and power dynamics of contested climate technologies - Livia Fritz; Lucilla Losi; Chad M. Baum; Sean Low; Benjamin K. Sovacool (Environmental Science & Policy, 2026)

Faster, higher, fairer? How multi-level instrumental justice reconfigures net-zero energy transitions in China - Weimin Zhang; Marfuga Iskandarova; Steve Griffiths; Benjamin K. Sovacool (Energy Policy, 2026)

The need for speed: mapping a conceptual typology for accelerating transitions toward sustainability - Kejia Yang; Allan Dahl Andersen; Benjamin K. Sovacool (Sustainability Science, 2026)

Beyond innovation and finance: Reviewing 25 years of United States climate change adaptation foreign aid objectives across 117 projects - Sheida Hooshmandi; Benjamin K. Sovacool (Climate and Development, 2026)

Acting without ownership: private-sphere energy efficiency practices in China - Erin Heinz; Weimin Zhang; Benjamin K. Sovacool; Thomas Kwan; Johan Nordensvärd; Frauke Urban; Muhammad Asif; Patrik Thollander; Patrik Rohdin; Niklas Arvidsson (Energy and Buildings, 2026)

Do clean energy transitions enhance global energy security? A comparative analysis of trends and tradeoffs across eight major economies, 1990-2020 - Shan Zhang; Benjamin K. Sovacool; Chu Wei (Energy Policy, 2026)

A multiplicity of tomorrows from ‘giving the world cancer’ to ‘colonizing space’: Imagining 299 climate intervention futures from a foresight exercise across 44 focus groups - Benjamin K. Sovacool; Livia Fritz; Chad M. Baum; Ramit Debnath; Roberto Cantoni; Francesc Martori (Environmental Science & Policy, 2026)

Of demographics, technology, and geography: The social determinants of energy consumption patterns and user behaviour in Saudi Arabia’s residential sector - Muhammad Asif; Benjamin K. Sovacool; Zulfiqar Ali; Erin Heinz; Thomas Alan Kwan; Johan Nordensvärd; Arunima Krishna; Patrick Thollander; Patrik Rohdin; Weimin Zhang (Energy and Buildings, 2026)

Conflicted about building decarbonization: Contested climate justice imaginaries in expert visions of low-carbon and net-zero buildings - Benjamin K. Sovacool; Erin Heinz; Thomas Kwan; Vincent Petit (Urban Climate, 2026)

Electric momentum? Catalyzing electric vehicle adoption in the United Arab Emirates - Steve Griffiths; Joao M. Uratani; Darrick Evensen; Benjamin K. Sovacool (Journal of Cleaner Production, 2026)

Harness gender empowerment to achieve climate justice, sustainability, and equity - Benjamin K. Sovacool; Jin In (Environmental Science & Policy, 2026)

The barriers and drivers to decarbonization of the building sector in the United States: Qualitative insights from Boston and Phoenix - Erin Heinz; Benjamin K. Sovacool; Thomas Kwan; Vincent Petit (Building and Environment, 2026)

Scaling carbon capture and storage (CCS) to gigaton capacity: A multi-dimensional and critical review - Benjamin Mitterrutzner; Benjamin K. Sovacool; Brage Rugstad Knudsen; Morgan D. Bazilian; Jinsoo Kim; Simon Roussanaly; Asgeir Tomasgard; Steven Griffiths (International Journal of Greenhouse Gas Control, 2026)

Social attitudes towards climate interventions: Are European publics uninformed about carbon removal and solar radiation management? - Benjamin K. Sovacool; Livia Fritz; Chad M. Baum; Lucilla Losi; Ramit Debnath; Hans Jakob Walnum; Finn Müller-Hansen; Elina Brutschin (Environmental Science & Policy, 2025)

Confronting a “silent killer:” reducing vulnerability to extreme heat in urban West Africa with surface cooling technology and climate-resilient roofing - Benjamin K. Sovacool (Climatic Change, 2025)
Extreme heat is a potent and progressively worsening public health problem confronting West Africa, where heat stress remains “a silent killer”. Most heat deaths occur in cities, driven by the urban heat island effect. In wealthier cities, air conditioning is the primary means of adapting to extreme heat, but Sierra Leone has one of the lowest electricity access rates in the world, making this climate intervention unaffordable and unreliable. One novel intervention to extreme heat is “Surface Cooling Technology” or “Surface Radiative Thermal Management” (SRTM). STRM interventions, unlike climate mitigation or adaptation, can produce very fast results, they do not involve politically difficult legislation, and they can involve modular and lower-risk technologies. This study explores the history, benefits, and challenges of one STRM pilot project, Mirrors for Earth’s Energy Rebalancing (MEER) in Freetown, Sierra Leone. MEER relies on a form of direct cooling technology to reduce urban heat by increasing albedo and infrared emissivity. To provide community benefits, MEER also makes furniture out of recycled PET bottles, which they give away at no cost so people can sit in the shade beneath the mirrors, alleviating exposure to extreme heat. The study is based on a qualitative research design involving: (a) site visits across Freetown ( N = 8), including three “slums” or informal settlements where they are putting mirrors and reflective surfaces to the greatest potential use to help vulnerable women and children; (b) N = 28 semi-structured interviews including community residents and members of local government; (c) a community survey, and (d) document analysis. In laying out the case study of MEER, the study aims to address a neglected focus on climate interventions to heat in urban areas in Sierra Leone and highlight the daily lived experiences of the poorest and most vulnerable residents of a city who struggle with extreme heat conditions.

Beyond environmental identity: Testing public support for novel carbon dioxide removal in Australia using structural modelling - Yuwan Malakar; Chad M. Baum; John Gardner; Kerryn Brent; Talia Jeanneret; Livia Fritz; Benjamin K. Sovacool (Journal of Environmental Management, 2025)

Exploring global climate intervention experiments: sociotechnical promises, innovation dynamics, and perceived co-impacts across 20 projects and pilots - Benjamin K. Sovacool; Chad M. Baum; Livia Fritz; Sean Low (Sustainability Science, 2025)
Using techniques commonly applied in participatory action research and ethnography, we examine 20 specific cases of experimentation for a selection of carbon removal and solar radiation modification interventions. These experiments include engineering-based approaches such as stratospheric aerosol injection, cloud brightening, carbon–neutral cement, biochar, direct air capture, and enhanced rock weathering alongside ecosystems-based approaches such as afforestation, seagrass restoration, and coral reef protection. Based on extensive original research of these 20 experimental projects—including 118 semi-structured research interviews and naturalistic site-based observation—we explore four questions. Firstly, what are the actor coalitions surrounding each experiment? Secondly, what promises and expectations do those actors generate? Thirdly, what innovation dynamics and styles are emergent and evident here? Finally, what perceived co-impacts are expected (by actors) to occur with widespread prospective deployment? Answering these questions in our empirical study offers insights into energy, climate, and climate intervention research, given that these experiments involve some of the most powerful and dominant actor coalitions, are supported by large amounts of climate finance investment, and will undoubtedly shape future deliberations over climate policy and technology deployment.

Realising a locally-embedded just transition: Sense of place, lived experience, and social perceptions of industrial decarbonisation in the United Kingdom - Benjamin K. Sovacool; Patrick Devine-Wright; Sarah Mander; Jordan Rowley; Stacia Ryder (Global Environmental Change, 2025)

Critically reviewing the 50 sociotechnical risks of building sector decarbonization: Conceptualizing risk as a proximity spiral - Erin Heinz; Benjamin K. Sovacool; Thomas Kwan; Vincent Petit (Energy and Buildings, 2025)

The industrial decarbonization paradigm: Carbon lock-in or path renewal in the United Kingdom? - Kyle S. Herman; Jeremy K. Hall; Benjamin K. Sovacool; Marfuga Iskandarova (Ecological Economics, 2025)

Climate policy, Least Developed Countries, and the Sustainable Development Goals: A critical review of SDG13 and infrastructural, institutional, and informational resilience - Gasser Hesham Seddik; Benjamin K. Sovacool (Environmental Science & Policy, 2025)

A novel model for barriers to electric vehicle adoption in the Middle East - Darrick Evensen; Joao M. Uratani; Benjamin K. Sovacool; Steve Griffiths (Transportation Research Part D: Transport and Environment, 2025)

Competing values, ideologies and lock-in dependencies in sociotechnical pathways for industrial decarbonization - Benjamin K. Sovacool; Steve Griffiths; Hans Jakob Walnum; Dylan Daniel Furszyfer; Marfuga Iskandarova (Environmental Science & Policy, 2025)

Between inflated expectations and inherent distrust: How publics see the role of experts in governing climate intervention technologies - Livia Fritz; Lucilla Losi; Chad M. Baum; Sean Low; Benjamin K. Sovacool (Environmental Science & Policy, 2025)

Reinventing the global oil capital: The sociotechnical dynamics of industrial net-zero megaprojects in Texas - Kyle S. Herman; Benjamin K. Sovacool (The Extractive Industries and Society, 2024)

Critical minerals mining and Native American sovereignty: Comparing case studies of lithium, copper, antimony, nickel and graphite mining in the United States - Macdonald Amoah; Benjamin K. Sovacool; Dustin Mulvaney; Morgan D. Bazilian; Richard Luarkie; Daniel Cardenas (The Extractive Industries and Society, 2024)

Toward just and equitable mobility: Socioeconomic and perceptual barriers for electric vehicles and charging infrastructure in the United States - Dong-Yeon Lee; Melanie H. McDermott; Benjamin K. Sovacool; Raphael Isaac (Energy and Climate Change, 2024)

“Made for corruption?” Private sector actors, renewable energy, and corruption risks for wind power in Mexico and solar electricity in Kenya - Benjamin K. Sovacool; Saul Mullard; Juan Camilo Ceballos (The Electricity Journal, 2024)

“We struggle to survive”: Exploring the whole systems energy injustices of solar photovoltaics in India - Benjamin K. Sovacool; Ryan Stock (The Electricity Journal, 2024)

Climate beliefs, climate technologies and transformation pathways: Contextualizing public perceptions in 22 countries - Livia Fritz; Chad M. Baum; Elina Brutschin; Sean Low; Benjamin K. Sovacool (Global Environmental Change, 2024)

“Oh Yes! Net-Zero”: Sociotechnical capabilities and regional innovation systems for British industrial decarbonization - Benjamin K. Sovacool; Kyle S. Herman; Marfuga Iskandarova; Jeremy K. Hall (Environmental Innovation and Societal Transitions, 2024)

The sociotechnical dynamics of blue carbon management: Testing typologies of ideographs, innovation, and co-impacts for marine carbon removal - Benjamin K. Sovacool; Chad M. Baum; Sean Low; Livia Fritz (Environmental Science & Policy, 2024)

Blinded by sunspots: Revealing the multidimensional and intersectional inequities of solar energy in India - Ryan Stock; Benjamin K. Sovacool (Global Environmental Change, 2024)

The political economy of net-zero transitions: Policy drivers, barriers, and justice benefits to decarbonization in eight carbon-neutral countries - Benjamin K. Sovacool; Dylan Furszyfer Del Rio; Weimin Zhang (Journal of Environmental Management, 2023)

Attention, sentiments and emotions towards emerging climate technologies on Twitter - Finn Müller-Hansen; Tim Repke; Chad M. Baum; Elina Brutschin; Max W. Callaghan; Ramit Debnath; William F. Lamb; Sean Low; Sarah Lück; Cameron Roberts; Benjamin K. Sovacool; Jan C. Minx (Global Environmental Change, 2023)

Expanding carbon removal to the Global South: Thematic concerns on systems, justice, and climate governance - Benjamin K. Sovacool (Energy and Climate Change, 2023)

Public support for decarbonisation policies: Between self-interest and social need for alleviating energy and transport poverty in the United Kingdom - Paul Upham; Neil Simcock; Benjamin Sovacool; Gerardo A. Torres Contreras; Kirsten Jenkins; Mari Martiskainen (Energy and Climate Change, 2023)

Corrigendum to “Building a green future: Examining the job creation potential of electricity, heating, and storage in low-carbon buildings” [Electr. J. 36(5) (2023) 107274] - Benjamin K. Sovacool; Darrick Evensen; Thomas A. Kwan; Vincent Petit (The Electricity Journal, 2023)

The demographics of energy and mobility poverty: Assessing equity and justice in Ireland, Mexico, and the United Arab Emirates - Jonathan Furszyfer Del Rio; Dylan D. Furszyfer Del Rio; Benjamin K. Sovacool; Steve Griffiths (Global Environmental Change, 2023)

Building a green future: Examining the job creation potential of electricity, heating, and storage in low-carbon buildings - Benjamin K. Sovacool; Darrick Evensen; Thomas A. Kwan; Vincent Petit (The Electricity Journal, 2023)

Inclusive innovation in just transitions: The case of smart local energy systems in the UK - Adrian Smith; Gerardo A. Torres Contreras; Marie-Claire Brisbois; Max Lacey-Barnacle; Benjamin K. Sovacool (Environmental Innovation and Societal Transitions, 2023)

Beyond climate stabilization: Exploring the perceived sociotechnical co-impacts of carbon removal and solar geoengineering - Benjamin K. Sovacool; Chad M. Baum; Sean Low (Ecological Economics, 2023)

What causes energy and transport poverty in Ireland? Analysing demographic, economic, and social dynamics, and policy implications - Christopher Lowans; Aoife Foley; Dylan Furszyfer Del Rio; Brian Caulfield; Benjamin K. Sovacool; Steven Griffiths; David Rooney (Energy Policy, 2023)

Determining our climate policy future: expert opinions about negative emissions and solar radiation management pathways - Benjamin K. Sovacool; Chad M. Baum; Sean Low (Mitigation and Adaptation Strategies for Global Change, 2022)
Negative emissions technologies and solar radiation management techniques could contribute towards climate stability, either by removing carbon dioxide from the atmosphere and storing it permanently or reflecting sunlight away from the atmosphere. Despite concerns about them, such options are increasingly being discussed as crucial complements to traditional climate change mitigation and adaptation. Expectations around negative emissions and solar radiation management and their associated risks and costs shape public and private discussions of how society deals with the climate crisis. In this study, we rely on a large expert survey ( N = 74) to critically examine the future potential of both negative emission options (e.g., carbon dioxide removal) and solar radiation management techniques. We designed a survey process that asked a pool of prominent experts questions about (i) the necessity of adopting negative emissions or solar radiation management options, (ii) the desirability of such options when ranked against each other, (iii) estimations of future efficacy in terms of temperature reductions achieved or gigatons of carbon removed, (iv) expectations about future scaling, commercialization, and deployment targets, and (v) potential risks and barriers. Unlike other elicitation processes where experts are more positive or have high expectations about novel options, our results are more critical and cautionary. We find that some options (notably afforestation and reforestation, ecosystem restoration, and soil carbon sequestration) are envisioned frequently as necessary, desirable, feasible, and affordable, with minimal risks and barriers (compared to other options). This contrasts with other options envisaged as unnecessary risky or costly, notably ocean alkalization or fertilization, space-based reflectors, high-altitude sunshades, and albedo management via clouds. Moreover, only the options of afforestation and reforestation and soil carbon sequestration are expected to be widely deployed before 2035, which raise very real concerns about climate and energy policy in the near- to mid-term.

Barriers, emotions, and motivational levers for lifestyle transformation in Norwegian household decarbonization pathways - Karen Richardsen Moberg; Benjamin K. Sovacool; Alexandra Goritz; Gaëtan M. Hinojosa; Carlo Aall; Maria Nilsson (Climatic Change, 2021)
Meeting the Paris Agreement targets requires strong near-term climate change mitigation in all sectors of the economy. Increasing demand-side emission abatement efforts is one important area to pursue, yet there are significant barriers that must be overcome in order to realize its potential. We ask: What barriers may be hindering deep emissions reduction at the household level? What kinds of levers are available to achieve emission reductions? Based on an original and extensive qualitative dataset, our in-depth study of households in Bergen, Norway, shows that individuals perceive they are confronted with considerable individual, economic, and infrastructural barriers that prevent them from taking deep mitigation actions. Our results however also suggest that some barriers can be overcome with motivational levers such as the availability of more sustainable alternatives, support networks and by the positive emotions felt when having a positive impact on the environment. Other barriers are more difficult to overcome, pointing to the overarching lesson from our study that households will need to be forced or incentivized beyond voluntary efforts to achieve rapid and comprehensive decarbonization. The current policy approach, aimed mostly at nudging for voluntary mitigation actions, is wholly inadequate to achieve significant emission reductions. Our study indicates that households are open for increasingly including more “sticks” into climate policymaking. While there are significant challenges to individuals taking stronger mitigation action, these can be overcome by strengthening government policies targeting the patterns and, importantly, volumes of household consumption.

A fair trade? Expert perceptions of equity, innovation, and public awareness in China’s future Emissions Trading Scheme - Jiangyue Joy Ying; Benjamin K. Sovacool (Climatic Change, 2021)
How can the Chinese emissions trading scheme (ETS) be redesigned or improved to better address issues of fairness and equity, innovation and learning, and awareness and social acceptance? In order to meet its 2030 carbon emission reduction pledges, the Chinese government has announced plans for a fully implementable national carbon ETS after 2020. This scheme is set to become the world’s most significant carbon trading market and it could cover half of all Chinese CO 2 emissions (as much as 4 billion tons of carbon dioxide). In this study, we qualitatively analyze the Chinese ETS through the lens of three interconnected themes—equity, innovation, and awareness—which are disaggregated into six specific dimensions. We then explore these themes and dimensions with a mixed methods and original research design involving a survey of 68 Chinese experts as well as 34 semi-structured research interviews with respondents from local governments, financial institutions, technology service companies, universities, industries, and civil society groups. We find that uneven economic and social growth could exacerbate any initial permits allocation scheme that could be a cornerstone for an ETS. Substantial technological and institutional uncertainties exist that could also hamper development and enforcement. Low or negative awareness among the public and private sector were identified as also being significant barriers for ETS implementation.

Decarbonization and its discontents: a critical energy justice perspective on four low-carbon transitions - Benjamin K. Sovacool; Mari Martiskainen; Andrew Hook; Lucy Baker (Climatic Change, 2019)

Climate change adaptation and the Least Developed Countries Fund (LDCF): Qualitative insights from policy implementation in the Asia-Pacific - Benjamin K. Sovacool; Björn-Ola Linnér; Richard J. T. Klein (Climatic Change, 2017)

Testing the efficacy of voluntary urban greenhouse gas emissions inventories - Fouad Khan; Benjamin K. Sovacool (Climatic Change, 2016)

All hands on deck: polycentric governance for climate change insurance - Connor P. Spreng; Benjamin K. Sovacool; Daniel Spreng (Climatic Change, 2016)

Left out in the cold: energy justice and Arctic energy research - Roman Sidortsov; Benjamin Sovacool (Journal of Environmental Studies and Sciences, 2015)

Nuclear accidents call for transdisciplinary nuclear energy research - Fabienne Gralla; David J. Abson; Anders P. Møller; Daniel J. Lang; Ulli Vilsmaier; Benjamin K. Sovacool; Henrik von Wehrden (Sustainability Science, 2015)

Microhydro electrification and climate change adaptation in Nepal: socioeconomic lessons from the Rural Energy Development Program (REDP) - Olivia Gippner; Saroj Dhakal; Benjamin K. Sovacool (Mitigation and Adaptation Strategies for Global Change, 2013)

They’ll be dammed: the sustainability implications of the Sarawak Corridor of Renewable Energy (SCORE) in Malaysia - Benjamin K. Sovacool; L. C. Bulan (Sustainability Science, 2013)

Perceptions of climate change risks and resilient island planning in the Maldives - Benjamin K. Sovacool (Mitigation and Adaptation Strategies for Global Change, 2012)

Expert views of climate change adaptation in the Maldives - Benjamin K. Sovacool (Climatic Change, 2012)

Building responsiveness to climate change through community based adaptation in Bangladesh - Amireeta K. Rawlani; Benjamin K. Sovacool (Mitigation and Adaptation Strategies for Global Change, 2011)

Sewing climate-resilient seeds: implementing climate change adaptation best practices in rural Cambodia - Anthony L. D’Agostino; Benjamin K. Sovacool (Mitigation and Adaptation Strategies for Global Change, 2011)

Improving adaptive capacity and resilience in Bhutan - Harsha Meenawat; Benjamin K. Sovacool (Mitigation and Adaptation Strategies for Global Change, 2011)

Environmental Damage, Abandoned Treaties, and Fossil-Fuel Dependence: The Coming Costs of Oil-and-Gas Exploration in the “1002 Area” of the Arctic National Wildlife Refuge - Benjamin K. Sovacool (Environment, Development and Sustainability, 2007)